The Effectiveness of the Canva Application in Learning Procedural Text Writing Skills for 7th Grade Students of SMP Negeri 27 Medan - Novisya Nayla; Nurul Asa; Raisya Mei Nabel Pakpahan; Stefany Indah Ayuri; Trisnawati Hutagalung; Nurul Azizah (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Procedure text is one of the narrative texts taught in grade 7 of junior high school (SMP/MTs) for both reading and writing aspects. On the other hand, the Canva application is one of the many applications frequently used in learning. This study aims to describe the effectiveness of the Canva application in learning procedural text writing skills. This study uses a quantitative descriptive method through a single-shot design, meaning that only one class is used as the object of research. This study was conducted in the odd semester of the 2025/2026 academic year at SMP Negeri 27 Medan. The population of this study were students of SMP Negeri 27 Medan who participated in procedural text writing skills learning using the Canva application. They were in one class with a total of 29 students. The sample was determined at 26 students based on a statistical formula. Sample members were selected by simple random selection without replacement from the population members. Data on learning outcomes of procedural text writing skills were collected using a test instrument designed using objective and systematic steps to meet the requirements of a valid test. A checklist was used to validate the scoring data and validate the results of the data analysis. Data on procedural text writing skills using the Canva application were analyzed using a paired sample t-test procedure. The results of the study show that the Canva application is effective for use in learning procedural text writing skills.